Indirect adaptive fuzzy control for industrial robots: A solution for contact applications. Issue 22 (1st December 2015) - Mendes, Nuno; Neto, Pedro
Highlights: It is proposed a systematic methodology to design adaptive fuzzy controllers. Robust control was achieved in robotic contact tasks. Knowledge about the plant improves control performance. Asymptotic convergence and stability are guaranteed by the hybrid controller. Abstract: Robots have been increasingly used in uncertain environments where direct contact with the surrounding environment exists. A design procedure of an adaptive fuzzy control, which can be carried out systematically, is suggested in this paper. The developed adaptive laws learn on-line the fuzzy rules of the control system and the uncertainties of the plant. Adaptive fuzzy control is integrated in a hybrid force/motion control system of an industrial robot to deal with a scenario of contact between the end-effector of the robot and a given surface. The controller is designed according to the previous knowledge about the process. The effectiveness of the proposed control system is shown through simulation and experimental results. Experimental results demonstrate superior stability and robustness of the proposed controller in relation to controllers of the same nature applied to industrial robotics, namely when there is contact between robot and surround environment.